A critical reflection on the judgement of the federal constitutional court of Germany on the European central bank's public sector purchase programme: ultra vires review and the primacy of European Law - Rademann, Philipp (Department of Public Law, 2022)
The financial politics of the European Union (EU) have been highly debated ever since the 2008 crisis, which left some European countries in financial turmoil. One part of the European financial policy has been the purchase of government bonds through the European Central Bank. The most vocal critics of this policy have for a long time emerged from Europe's biggest economy – Germany. A case against the purchase of government bonds was eventually brought to the Federal Constitutional Court of Germany (FCC). The FCC referred the matter to the European Court of Justice, which in 2018 upheld the practice and found it legal. In May of 2020 the FCC went against the European Court of Justice and pronounced the practice of purchasing government bonds as well as the decision upholding it to be ultra vires. Although there have been other domestic courts within the EU that have overruled EU law, last years's verdict was unique in its blatant defiance of the European institutions and the primacy of EU Law. This paper analyses the two judgements with a focus on the issues of the ultra vires review as well as the primacy of EU law. By scrutinising the FCC's case law on the issue, the author argues that the FCC's judgement is inconsistent with its own jurisprudence, and the case substantially unsuited and unwisely chosen for rendering the ultra vires verdict for the first time. Moreover, the judgement completely disregards the primacy of EU law, which not only questions the equality of EU Members but ultimately jeopardises one of the most crucial principles of the Union.